Freedom and Responsibility in the University - Diaz, Jesus (Silliman Journal, 2024)
The freedom we speak of, the freedom to which the university and the various elements with-in it are entitled, is not, and cannot be, an absolute freedom. To think so would be to admit that this freedom is the highest good. It has its limits, firstly, in that the university exists for the common rood. . .and in that the various elements within the university have rights of their own,” according to this educator.